INTEGRATION OF PRODUCT-BASED LEARNING AND UPCYCLED MATERIALS IN MATHEMATICS LEARNING IN ELEMENTARY SCHOOLS - Anik Wulandari; Cerianing Putri Pratiwi; Heny Kusuma Widyaningrum; Endang Sri Maruti (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to examine the effectiveness of product-based learning with upcycled materials in improving elementary school students’ mathematics learning outcomes on bar chart material.Methodology – The study employed a classroom-based, iterative research design implemented across several learning phases to optimize the learning process and outcomes. The participants were 37 fourth-grade students with heterogeneous academic abilities. We collected data through learning outcome tests, observations, and documentation, and analyzed them using quantitative and qualitative approaches.Findings – The results showed a significant increase in student learning outcomes. The average score increased from 63.8 in the initial phase to 72.4, then to 84.1 in the final phase. The percentage of learning completion also increased from 37.8% to 62.2%, then to 89.2%, exceeding the established learning effectiveness criteria. The findings indicate that integrating product-based learning with upcycled materials improves learning outcomes and strengthens students' conceptual understanding through active, contextual, and meaningful learning activities. Students’ active involvement supported by concrete media enabled deeper knowledge construction and reinforced the constructivist learning approach.Contribution – This study contributes to the development of innovative mathematics learning by integrating product-based learning with environmentally based learning media, providing an alternative contextual learning approach that supports student engagement, creativity, and environmental awareness in elementary education.